Post-transplant lymphoproliferative disorder presented with diplopia; Diagnosis by FDG-PET/CT - Saki Sagara, MD; Kenichiro Otsuka, MD; Ryuichi Shimada, MD; Masao Iwao, MD; Shuhei Honda, MD; Kazuki Okuhiro, MD; Masaki Yoshida, MD; Tsutomu Daa, MD; Yoshiki Asayama, MD (Radiology Case Reports)
Post-transplant lymphoproliferative disorder (PTLD) is a general term describing lymphoproliferative disorders that develop against the background of immunosuppression after organ transplantation, and that range from benign tumors to malignant lymphoma. PTLD is relatively rare after liver transplantation, and there are few cases of post-liver transplant lymphoma with lesions in the clivus. We here describe the case of a patient who visited our hospital complaining of diplopia after a liver transplant. Fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) revealed lesions with high FDG uptake in the clivus and throughout the body, and the patient was diagnosed with lymphoproliferative disease after liver transplantation. The diplopia was thought to have been caused by the clivus lesion infiltrating into the abducens nerve. In patients after organ transplantation, care must be taken to watch for onset of PTLD, and FDG-PET/CT is thought to be useful for its diagnosis.